2021
DOI: 10.1002/mas.21763
|View full text |Cite
|
Sign up to set email alerts
|

Collision energies: Optimization strategies for bottom‐up proteomics

Abstract: Mass‐spectrometry coupled to liquid chromatography is an indispensable tool in the field of proteomics. In the last decades, more and more complex and diverse biochemical and biomedical questions have arisen. Problems to be solved involve protein identification, quantitative analysis, screening of low abundance modifications, handling matrix effect, and concentrations differing by orders of magnitude. This led the development of more tailored protocols and problem centered proteomics workflows, including advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 184 publications
0
29
0
1
Order By: Relevance
“…This approach is expected to provide several benefits, as some of us discussed in a recent review for other related analytes. 27 We further leveraged the resulting glycopeptidelevel information to design optimized measurement strategies, confirming the importance of both fine-tuning itself and using a diverse set of N-glycopeptide species for this purpose. Finally, our study is the first to provide reference data based on wellchosen standard materials for the transfer of the optimized method between mass spectrometers, which can guide scientists in choosing optimal settings on their experimental platforms in a laboratory or in a pharmaceutical industrial setting.…”
Section: ■ Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…This approach is expected to provide several benefits, as some of us discussed in a recent review for other related analytes. 27 We further leveraged the resulting glycopeptidelevel information to design optimized measurement strategies, confirming the importance of both fine-tuning itself and using a diverse set of N-glycopeptide species for this purpose. Finally, our study is the first to provide reference data based on wellchosen standard materials for the transfer of the optimized method between mass spectrometers, which can guide scientists in choosing optimal settings on their experimental platforms in a laboratory or in a pharmaceutical industrial setting.…”
Section: ■ Introductionmentioning
confidence: 70%
“…In addition, though both studies used a QTof mass spectrometer from Bruker, instrumental differences may also contribute, as we have seen in the past for closely related Orbitrap instruments. 27 Different internal energy distribution on the two instruments, caused by differences of the ESI source (e.g., cone voltage and gas pressures) or voltages applied during ion transfer might be relevant candidates. 43−45 We note here that the different collision energy selection methods actually lead to perceivable differences at the level of individual peptides.…”
Section: Comparison To Literature Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that larger proteoforms may need a higher energy for efficient backbone fragmentation. 45 A 22 kDa intact proteoform of Stathmin (STMN1, Uniprot#P16949) was shown as an example in Figure 5. The observed monoisotopic mass was 22358.55 Da with a mass measurement accuracy of 5.96 ppm compared with the theoretical mass of 22358.42 Da.…”
Section: Evaluation Of the Effect Of Normalized Hcd Fragmentation Ene...mentioning
confidence: 99%